The impact of COVID-19-related information scanning via social media on Chinese intentions regarding coronavirus vaccinations - Cheng, Cheng; Espanha, Rita (Frontiers in Communication, 2023)
Background: During the COVID-19 health crisis, there is a recognized need for addressing vaccine hesitancy to increase vaccination rates globally. In this context, exploring the underlying public behavioral mechanism related to COVID-19 vaccine decisions has been the focus of much investigation. Objective: This thesis seeks to investigate and explain the impact of COVID-19-related information scanning via social media on health perceptions and behavioral intentions to receive COVID-19 vaccine doses in China. Methods: By distributing a questionnaire online, 483 respondents were recruited. Then, the present study applied partial least squares structural equation modeling (PLS-SEM) by using Smart PLS 3.3. Finally, the variance of path relationships among different socio-demographic groups was tested by performing multigroup analysis. Results: COVID-19 information scanning via social media has a positive influence on four constructs, including perceived severity (β=0.355,p<0.01), perceived vulnerability (β=0.140,p<0.05), self-efficacy (β=0.360,p<0.01) and response efficacy (β=0.355,p<0.01). No significant correlation was found between threat appraisal and behavioral intentions to get vaccinated, including perceived severity and perceived vulnerability. And scanned information exerts influence through other significant factors, including self-efficacy (β=0.379,p<0.01), response efficacy (β=0.275,p<0.01) and response cost (β=-0.131,p<0.05). Additionally, response efficacy exerts stronger influences on men’s behavioral intentions, whereas response cost and perceived vulnerability are stronger mediators among women. Surprisingly, scanned information is positively associated with response cost among older adults, and perceived vulnerability was negatively associated with behavioral intentions to receive the coronavirus vaccines among younger adults. And there were significant differences in the association of perceived vulnerability and behavioral intentions between lower and higher educated groups. Conclusions: The present results highlight the key roles of COVID-19-related scanned information on public health perceptions and behavioral intentions. Tailored health communication must deliver factual information, address the public uncertainty regarding adverse effect of COVID-19 vaccine, and clarify vaccine schedules.